Protection Of Children From Violence In Social Media In The New Normal Era - Aryono; Prastyanti, Rina Arum (VJJ, 2020)
The Ministry of Women's Empowerment and Child Protection (PPPA) received thousands of reports related to cases. Most of the reports submitted were about sexual violence. Deputy for Child Protection of the Ministry of PPPA, from the Online Information System for the Protection of Women and Children (Symfoni PPA) which was collected from January 1 to July 31, 2020. In total there were 4,116 cases. The number has increased as per 18 August 2020 to 4,833 cases. Most reports were submitted from East Java, East Kalimantan, Southeast Sulawesi, and North Maluku. In detail, the 4,116 cases received by the PPA Symphony consisted of 68 victims of exploitation, 73 victims of TIP, 346 victims of neglect, 979 victims of psychological violence, 1,111 victims of physical violence and 2,556 victims of sexual violence. This type of research uses the sociolegal research method. This research requires a multidisciplinary approach to analyze and interpret the law, the legal phenomenon, the relationship between those two and also their relationship with the society in its widest sense. The research approach used in this paper is the statute approach. The statute approach is carried out by examining all laws and regulations relating to the legal issues being addressed. The research conducted is aimed more at the approach to laws and regulations associated with the issue protection of children from violence in social media in the new normal era. Data Analysis Techniques used for this study are deductive analysis methods, namely data analysis methods starting with general postulates and certain paradigms as a base for starting conclusions. National governments are urged to devise and implement legislation and to harmonise laws to protect children from all cyber crimes including online grooming, luring or stalking, exposure to illegal or inappropriate materials and all actions related to child pornography (including creation, dissemination, accessing, downloading, possession and incitement). As such, governments are urged to classify the crime of being involved (in any way) with child pornography as a crime against humanity, thereby falling under the principle of universal jurisdiction. Cross-border cooperation Cross-border jurisdictional issues remain a barrier for achieving comprehensive solutions.